PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE COOPERATIF INTERGRATED READING AND COMPOSITION (CIRC) UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PUISI PADA SISWA SEKOLAH DASAR - Amelia, Rossa; Mustamiroh, Mustamiroh (LPPM UM Metro, 2024)
This research was motivated by the low learning outcomes of class IV students at SD Negeri 004 Barong Tongkok for the 2022/2023 academic year, especially in Indonesian language content. The aim of this research is to determine the improvement in Indonesian language learning outcomes in poetry reading material using a cooperative model of the Cooperative Integrated Reading and Composition type for fourth grade students at SD Negeri 004 Barong Tongkok for the 2022/2023 academic year. This type of research is Classroom Action Research (PTK) which is carried out in two cycles and each cycle consists of two meetings. This research was carried out in the even semester of the 2022/2023 academic year at SD Negeri 004 Barong Tongkok. The subjects of this research were the teachers and students of class IV-A SDN 004 Barong Tongkok, totaling 22 students and the object of this research was poetry reading skills using the Cooperative Type of Integrated Reading and Composition model. This research procedure consists of four stages, namely planning, implementation, observation and reflection. The data collection techniques used are observation, tests and documentation. Data analysis techniques in this research use average values, percentages, test scores and graphs. The data collection technique used in this research uses several techniques, namely observation, test (evaluation) and documentation techniques H. Data Analysis Techniques. The data analyzed in this research are students' learning outcomes based on the final grades in each cycle. Classroom action research data analysis techniques are carried out through observation and tests. The data obtained was then compiled, explained and analyzed descriptively using averages and percentages. The research results showed that the average score in the pre-cycle was 71.95 with a percentage of students who completed 35% (9 students), then experienced an increase in the first cycle of 0.44 from the pre-cycle score with an average student learning outcome of 72. 27 and the percentage of students who completed was 35% (9 students). In cycle II the average score increased by 25.8 from cycle I with an average score of 90 with a percentage of students who completed 80% (19 students). Based on the research results, it can be concluded that there is an increase in poetry reading skills with the Cooperative Model, Integrated Reading And Composition Type, in class IV students at SD Negeri 004 Barong Tongkok for the 2022/2023 academic year.